Geneza rynku papierów wartościowychw Polsce - Łagowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Warsaw Stock Exchange, in its present form, has existed for more than 22 years. Despite its short modern history, a tradition of Polish capital market could be observed far earlier. To prove this theory, the author presents the history of public trading in securities in Poland
Keywords: capital market; emergence of securities markets; Warsaw Stock Exchange